Bridge shelter care and rehabilitation boarding facility for vulnerable youth - Malabanan, Jewel Jade S. (College of Architecture, University of the Philippines Diliman, 2025)
The high prevalence of abuse, neglect, and exploitation among children in the Philippines, coupled with the detrimental effects of early trauma on brain development, underscores the urgent need for effective rehabilitation and care systems, advocating for safe spaces and community support to aid recovery. This study explores architectural solutions that integrate education, therapy, and skill-building within a boarding facility to address the unique developmental needs of vulnerable youth. Using a trauma-informed design (TID) approach, the study aims to create environments that foster safety, comfort, and inclusivity, promoting healing and social reintegration. The primary research question investigates how architecture can facilitate a cohesive, trauma-informed environment, while secondary questions examine the integration of education, therapy, and skill-building spaces, the balance of privacy and social interaction, and the transition from institutional care to independence. These inquiries aim to inform design strategies that holistically support rehabilitation and empowerment. Research methods include desk research, literature reviews, and interviews, that will be analyzed through thematic and content analysis, to understand user behavior and align with standards and guidelines. The initial findings and assumptions are synthesized into an architectural program centered on TID principles, ensuring spaces that promote autonomy and healing. Initial findings emphasize the importance of reclaiming a sense of autonomy for vulnerable youth in the physical design of spaces. The project translates these insights into an architectural design that integrates education, therapy, and vocational training in a cohesive and supportive environment. By addressing the urgent need for holistic support systems, the study contributes to the design of facilities that enhance healing, safety, and empowerment, ultimately preparing vulnerable youth for social reintegration and independence.